Motion-driven self-powered hydrogel nanofiber patch as well as preparation method and application thereof

By introducing motion-driven self-powered hydrogel nanofibers and anti-inflammatory/antioxidative properties in self-powered skin patches, the problem of insufficient effectiveness in complex wounds and inflammatory environments is solved, achieving greater efficiency wound healing and biocompatibility.

CN119455053AActive Publication Date: 2025-02-18UNIVERSITY OF HEALTH & REHABILITATION SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411651830.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The existing self-powered skin patches are not effective in complex irregular wound scenes and inflammatory environments, and the material is not degradable and difficult to fit perfectly with the wound, affecting the healing effect.

Method used

Develop a motion-driven self-powered hydrogel nanofiber patch that is prepared through the piezoelectric effect of barium titanate and the anti-inflammatory/antioxidative properties of tannin, combined with electrospinning technology to achieve the piezoelectric response of the patch and biocompatibility.

Benefits of technology

This patch can generate electrical stimulation through daily movement drive, promote wound healing, reduce inflammatory response, and form a state close to the initial skin. It is suitable for healing of wounds of all sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455053A_ABST
    Figure CN119455053A_ABST
Patent Text Reader

Abstract

The invention discloses a motion-driven self-powered hydrogel nanofiber patch as well as a preparation method and application thereof, and the motion-driven self-powered hydrogel nanofiber patch is developed by comprehensively utilizing the anti-inflammatory / antioxidant effects of GelMA hydrogel nanofiber and TA and the piezoelectric effect of tetragonal barium titanate. Wound healing can be accelerated by adjusting immune response, regulating inflammation and promoting cell proliferation and adhesion, and a state closest to the initial skin is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a motion-driven self-powered hydrogel nanofiber patch and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to increase some understanding of the overall background of the invention, and should not be necessarily regarded as an admission or any form of suggestion that the information constitutes the prior art already known to ordinary technicians in this field.

[0003] Skin wounds are common in accidental injuries. Slow healing and scarring can seriously affect daily life. Attention should be paid to wound healing. On the one hand, it is necessary to ensure accelerated re-epithelialization, collagen deposition and angiogenesis; on the other hand, excessive inflammation of the wound should be prevented, which will cause scar formation. Under the action of external force, mechanical deformation is continuously generated to generate electrical stimulation to directly act on the wound, but it is very difficult to prepare self-powered skin patches with good biological functions to cope with wound healing and play the dual role of biomaterials and electrical stimulation. For this reason, researchers have developed piezoelectric properties for biomaterials (DOI: 10.1002 / smll.202301981), and on this basis, active molecules are further modified to give skin patches additional functions, such as anti-inflammatory / antioxidant (DOI: 10.1021 / acsami.6b10491). However, traditional self-powered skin patches generally focus on piezoelectric response. Although it has certain effects, it is limited by the material itself. For example, the material itself is non-degradable and difficult to fit perfectly with the wound. Complex irregular wound scenes and inflammatory environments have not yet received attention from researchers. For patients with chronic wounds, slow wound healing is also a clinical problem that needs to be urgently addressed. Summary of the invention

[0004] In view of the shortcomings of the existing technology and the mechanical deformation caused by daily movement, the present invention has developed a motion-driven, self-powered hydrogel nanofiber patch based on the piezoelectric response characteristics of mechanical deformation and the piezoelectric effect of barium titanate, and on this basis, the patch is endowed with anti-inflammatory / antioxidant capabilities to synergistically accelerate the wound healing process and solve the various problems faced by wounds inside the body.

[0005] The technical solution adopted by the present invention is as follows:

[0006] In a first aspect of the present invention, a method for preparing a motion-driven self-powered hydrogel nanofiber patch is provided, the method comprising the following steps:

[0007] (1) preparing a spinning solution, wherein the solute is GelMA (gelatin methacrylate anhydride) and tetragonal barium titanate nanoparticles, and obtaining piezoelectric nanofibers after electrospinning;

[0008] (2) drying the piezoelectric nanofibers in step (1), and then immersing the dried piezoelectric nanofibers in a photo-crosslinking solution to crosslink them under ultraviolet irradiation to obtain piezoelectric hydrogel nanofibers;

[0009] (3) The piezoelectric hydrogel nanofibers are immersed in a TA (tannic acid) mixed solution, and then taken out to obtain a functionally modified piezoelectric hydrogel fiber patch, which is the motion-driven self-powered hydrogel nanofiber patch of the present invention.

[0010] In one or some embodiments of the present invention, in step (1), the degree of substitution of GelMA is 0-100%, excluding 0; preferably, the degree of substitution of GelMA is 10-80%; more preferably, the degree of substitution of GelMA is 60%.

[0011] In one or some embodiments of the present invention, in step (1), the amount of tetragonal barium titanate nanoparticles added is 0-50% (w / v), excluding 0, which means that 0-50g of tetragonal barium titanate nanoparticles are added to 100mL of solution (with GelMA solution added); preferably, the amount of tetragonal barium titanate nanoparticles added is 0.1-20% (w / v); more preferably, the amount of tetragonal barium titanate nanoparticles added is 0.25% (w / v). The addition of tetragonal barium titanate will affect the piezoelectric properties of the material, and the increase of barium titanate can improve the piezoelectric output. However, when the concentration of barium titanate is too high, its biocompatibility will be reduced. After experimental verification, 0-50% (w / v) is selected.

[0012] In one or some embodiments of the present invention, in step (1), the solvent of the spinning solution is HFIP (hexafluoroisopropanol), and the concentration of the spinning solution is 1-20% (w / v), which means that 1-20 g of GelMA is added to 100 mL of HFIP.

[0013] In one or some embodiments of the present invention, in step (1), the electrospinning parameters are: voltage 9-10 kV, injection rate 20 μL / min, receiving distance 20 cm, drum speed 200 rpm, and environmental conditions maintained at 20-25° C. and 25-30% humidity.

[0014] In one or some embodiments of the present invention, in step (2), in order to obtain piezoelectric hydrogel nanofibers with good cross-linking effect, the photocross-linking solution is prepared by dissolving a photoinitiator in anhydrous ethanol, and the concentration of the photocross-linking solution is 1-20% (w / v), which means that 1-20g of photoinitiator is dissolved in 100mL of anhydrous ethanol; preferably, the solubility of the photocross-linking solution is 1-10% (w / v); more preferably, the solution concentration is 5% (w / v).

[0015] Preferably, the photoinitiator is Irgacure 2959.

[0016] In one or some embodiments of the present invention, in step (2), during the cross-linking treatment, 365 nm ultraviolet irradiation is performed for 1 to 300 min; preferably, the ultraviolet irradiation is performed for 1 to 100 min; more preferably, the ultraviolet irradiation is performed for 10 min.

[0017] In one or some embodiments of the present invention, in step (3), the TA mixed solution is prepared by dissolving tannic acid in Tris-HCl buffer, and the concentration is 1 to 20 mg / mL; preferably, the concentration of the TA (tannic acid) mixed solution is 8 mg / mL.

[0018] In one or some embodiments of the present invention, in step (3), slight shaking is performed during soaking, and the shaking frequency is 10 to 1000 rpm.

[0019] In a second aspect of the present invention, a motion-driven self-powered hydrogel nanofiber patch prepared by the above method is provided.

[0020] Preferably, it is used for skin repair.

[0021] In the third aspect of the present invention, there is provided the use of the hydrogel nanofiber patch in the preparation of medical supplies.

[0022] Preferably, the hydrogel nanofiber patch is used in the preparation of skin repair products. Compared with the related technologies known to the inventors, one of the technical solutions of the present invention has the following beneficial effects:

[0023] The present invention develops a motion-driven self-powered hydrogel nanofiber patch by comprehensively utilizing the piezoelectric effect of GelMA hydrogel nanofiber and tetragonal barium titanate.

[0024] The present invention comprehensively utilizes the anti-inflammatory / antioxidant effects of GelMA hydrogel nanofibers, TA and the piezoelectric effect of tetragonal barium titanate to develop a motion-driven self-powered hydrogel nanofiber patch, which can accelerate wound healing by regulating immune response, inflammation, and promoting cell proliferation and adhesion, forming a state closest to the initial skin.

[0025] The present invention can not only continuously generate electrical stimulation under the drive of daily exercise to simulate the endogenous bioelectric field to promote wound healing, but also can provide a suitable cell survival environment by biomimetic extracellular matrix. At the same time, the good antioxidant / anti-inflammatory properties brought by TA can achieve immune regulation and inflammation regulation to accelerate wound healing. The preparation cost is low with electrospinning technology, and it can adapt to wounds of various sizes. In addition to skin injuries, it has more application advantages in scenarios such as blood vessel and heart patches inside the body to promote tissue repair.

[0026] The motion-driven self-powered hydrogel nanofiber patch of the present invention has the following functions: 1) The unique hydrogel nanofiber structure imitates the natural extracellular matrix environment to create a microenvironment most suitable for cell growth. The inflammatory response regulated by TA prevents the occurrence of excessive inflammation, which is crucial for patients with chronic diseases. It can prevent the infection and scar formation caused by the persistent non-closure of the wound and promote wound repair; 2) The motion-driven self-powered hydrogel nanofiber converts mechanical energy into electrical stimulation to accelerate wound closure. Electrical stimulation that promotes wound healing can be generated remotely at any time, simulating endogenous bioelectric fields to solve various complex wound problems, while dealing with wounds of different sizes. Figure 1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.

[0028] Figure 1 Schematic diagram of the hydrogel nanofiber patch of the present invention promoting skin healing.

[0029] Figure 2 Schematic diagram of the preparation principle of the hydrogel nanofiber patch of the present invention.

[0030] Figure 3 Morphological observation. GelMA: GelMA hydrogel nanofibers; Piezo: T-BTO-doped GelMA hydrogel nanofibers; Piezo@TA / Nonpiezo@TA: piezoelectric / non-piezoelectric hydrogel nanofibers with TA coating on the surface.

[0031] Figure 4 Analysis of material properties and piezoelectric effect: (ab) Optical images and quantitative curves of water contact angle changing with time; (c) shape memory effect; (d) height, piezoelectric amplitude and phase images of barium titanate nanoparticles; (eg) piezoelectric properties of tetragonal barium titanate nanoparticles; (hi) piezoelectric response of Piezo and Piezo@TA to different pressures; (j) comparison of piezoelectric response of different materials under 25N.

[0032] Figure 5 Material biocompatibility evaluation: (a) cell viability, cell adhesion (30 min) and cell spreading (24 h); (b) intracellular ROS expression and changes in mitochondrial membrane potential.

[0033] Figure 6 Piezoelectric hydrogel nanofiber patch promotes skin healing: (a) Wound healing after different treatments; (b) Changes in wound healing marks and healing rate curve.

[0034] Figure 7 TA-modified piezoelectric hydrogel nanofiber patch promoted wound repair on the 14th day: (a) histological staining, immunofluorescence and immunohistochemistry; (bg) quantitative analysis.

[0035] Figure 8 TA-modified piezoelectric hydrogel nanofiber patch promoted wound repair on the 14th day: (a) two-photon microscopy image of regenerated tissue; (b) quantitative analysis. DETAILED DESCRIPTION

[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0038] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0039] Example 1

[0040] The schematic diagram of the preparation principle is as follows Figure 2 .

[0041] ① GelMA nanofiber bundles were prepared by stable jet electrospinning technology: GelMA (substitution degree of 60%) was weighed and dissolved in HFIP solution to prepare a spinning solution with a concentration of 5% (w / v). In order to give GelMA hydrogel nanofibers piezoelectric properties, 0.25% (w / v) tetragonal barium titanate nanoparticles (T-BTO) were added to the spinning solution, and then ultrasonicated for 15 minutes to ensure uniform dispersion, stirred on a magnetic stirrer for more than 12 hours until a uniform solution was formed, and ultrasonicated again for 15 minutes before electrospinning. Piezoelectric nanofibers were then prepared based on the electrospinning method, with spinning parameters: voltage 9-10kV, injection rate 20μL / min, receiving distance 20cm, drum speed 200rpm, and environmental conditions maintained at 20-25°C and 25-30% humidity. To induce the formation of hydrogel nanofibers, the dried GelMA nanofibers with T-BTO added were soaked in a photocrosslinking solution (Irgacure 2959 dissolved in anhydrous ethanol, the solution concentration was 5% (w / v)) and irradiated with 365nm ultraviolet light for 10min to induce crosslinking. Subsequently, the fibers were washed with anhydrous ethanol to remove excess photoinitiator to obtain piezoelectric hydrogel nanofibers.

[0042] ②TA functional modified hydrogel nanofibers: dissolve tannic acid (TA, 8 mg / mL) in Tris-HCl (10 mM, pH 8.5) buffer to prepare a TA mixed solution; then immerse the piezoelectric hydrogel nanofibers in the solution and gently oscillate at room temperature for 12 hours at an oscillation frequency of 100 rpm; take out the hydrogel nanofibers and wash them with ultrapure water for several times to obtain a piezoelectric hydrogel fiber patch modified with TA function.

[0043] like Figure 3 As shown, the GelMA hydrogel nanofiber membrane (named GelMA) and the hydrogel nanofiber membrane endowed with piezoelectric properties (named Piezo) prepared by the stable jet electrospinning technology both show a smooth surface; the piezoelectric / non-piezoelectric hydrogel nanofiber (named Piezo@TA / Nonpiezo@TA) modified by TA function has a thicker fiber diameter and presents an uneven fiber surface. These results show that the present invention successfully prepared the piezoelectric / non-piezoelectric and TA functional modified GelMA hydrogel fiber membrane.

[0044] like Figure 4 As shown in (a), the hydrophilicity of the hydrogel nanofibers modified with TA is significantly improved, which helps cells transport nutrients and metabolites. Quantitative analysis of the optical images shows Figure 4 (b) more intuitively reflects the change in the hydrophilicity of the hydrogel nanofibers. The mechanical properties of the fiber membrane changed significantly, indicating that tannic acid and barium titanate nanoparticles can change the mechanical properties of the piezoelectric hydrogel fiber membrane ( Figure 4 (c)); Subsequently, the present invention analyzed the piezoelectric properties of barium titanate nanoparticles and found that tetragonal barium titanate nanoparticles are beneficial to improving the piezoelectric properties of hydrogel nanofibers. Although cubic barium titanate nanoparticles have certain piezoelectric properties, they are still far lower than tetragonal barium titanate nanoparticles ( Figure 4 (dg)), which proves that tetragonal barium titanate has the potential to endow hydrogel nanofibers with piezoelectric properties; when the piezoelectric hydrogel nanofibers are placed under different pressures, it is found that the piezoelectric output generated by the increase in pressure changes significantly ( Figure 4 (h)), the piezoelectric effect weakens to a certain extent after TA modification ( Figure 4 (i)). This may be attributed to the fact that TA makes the fiber network denser, resulting in smaller mechanical deformation under the same force, and TA has a certain binding and neutralizing effect on the generated electrons. Similarly, under the same force of 25N, the hydrogel nanofiber membrane without barium titanate has no piezoelectric effect, and the one doped with Nonpiezo@TA also has some changes ( Figure 4 (j)). These results indicate that tetragonal barium titanate can endow hydrogel nanofibers with good piezoelectric properties, and the hydrogel nanofiber membrane modified by TA has better hydrophilicity and is more suitable for cell proliferation and growth.

[0045] like Figure 5 As shown in (a), live-dead staining revealed that all material groups showed good cell compatibility, among which the Piezo@TA modified group had the largest proportion of live cells. At the same time, GelMA hydrogel nanofibers can promote fibroblast adhesion, and the promotion effect is further enhanced after TA and piezoelectric functional modification; similarly, when the cells are cultured for 24 hours, it can be observed that Piezo@TA modification significantly enhances the stress fiber remodeling of the cells and is also conducive to the formation of the cytoskeleton. From a functional point of view, TA modification can give the material antioxidant / anti-inflammatory ability, remove intracellular ROS to prevent inflammation and maintain the normal functional expression of mitochondria ( Figure 5 (b)).

[0046] like Figure 6 As shown in (a), the Piezo@TA patch is attached to the wound. The mechanical deformation caused by the daily movement of the mouse causes the patch to produce electrical stimulation seams, thereby promoting wound healing. The wound was observed until 14 days. It can be seen that in the untreated Blank group, obvious unclosed areas can still be seen at the wound ( Figure 6 (a)); the healing rate of the Piezo@TA wound was significantly improved, and at 14. Interestingly, the healing rate of the Nonpiezo@TA group was also significantly higher than that of the Blank group ( Figure 6 (b)). This indicates that Piezo@TA promotes wound healing through the combined effect of electrical stimulation and TA-modified hydrogel nanofibers.

[0047] like Figure 7 (a) Analysis of wound changes over 14 days. Compared with the Blank group, hydrogel nanofiber treatment significantly promoted tissue remodeling in the wound area. It was observed that Piezo@TA significantly promoted skin regeneration, and wound healing was basically achieved under electrical stimulation, with obvious epithelialization ( Figure 7 (b)). Masson staining results also confirmed that hydrogel nanofibers can promote collagen formation, and Nonpiezo@TA can also promote collagen remodeling and maturation at the same time. This phenomenon is further enhanced under electrical stimulation (Piezo@TA, Figure 7 (c)). The results of PCNA / Integrinβ1 and CD31 immunofluorescence staining further confirmed that Piezo@TA patch can significantly promote the proliferation of new cells and guide cell migration for epidermal remodeling under electrical stimulation ( Figure 7 (de)), considering that the density of CD31-positive capillaries decreased significantly during the remodeling phase Figure 7 (f), indicating that electrical stimulation of hydrogel nanofibers can accelerate skin healing and promote the wound to enter the remodeling stage. In addition, the TGF-β / IL-6 ratio of the Piezo@TA group was the highest ( Figure 7 (g) ), indicating that a sustained anti-inflammatory microenvironment is beneficial for wound healing.

[0048] like Figure 8 (a) Analysis of skin changes after repair. Compared with the Blank group, the regenerated epidermal tissue induced by the hydrogel nanofiber patch is very similar to the skin of normal rats. Under the dual effects of electrical stimulation and materials, Piezo@TA forms neatly arranged collagen fibers and elastic fibers, which indicates that electrical stimulation has a guiding effect on cell behavior and extracellular matrix remodeling. Specifically, since excessive thickness of the stratum corneum (SC) will delay wound healing, the Blank group showed an increase in SC thickness and a decrease in the density of the granular layer (DSG) compared with normal skin tissue ( Figure 8 (b-c)). Therefore, after Piezo@TA and non-Piezo@TA treatment, SC and DSG were very similar to those of normal skin. The second harmonic generation (SHG)-autofluorescence (AF) dermal aging index (SAAID) reflects the changes in the average strength of collagen fibers and elastic fibers. Compared with the non-Piezo@TA group, the SAAID and dermal-epidermal junction index (DEJI) values ​​detected in the Piezo@TA group were closer to those of the original skin ( Figure 8 (e)). It can be seen that the regenerated tissue is closest to the natural tissue under the dual effects of electrical stimulation and materials.

[0049] In summary, the present invention successfully prepared a motion-driven self-powered hydrogel nanofiber patch, and proved that it can not only accelerate wound closure by utilizing its own performance, but also generate electrical stimulation under motion drive, further accelerating wound repair.

[0050] Example 2

[0051] ① GelMA nanofiber bundles were prepared by stable jet electrospinning technology: GelMA (substitution degree 65%) was weighed and dissolved in HFIP solution to prepare a spinning solution with a concentration of 10% (w / v). In order to give GelMA hydrogel nanofibers piezoelectric properties, 10% (w / v) tetragonal barium titanate nanoparticles (T-BTO) were added to the spinning solution, and then ultrasonicated for 20 minutes to ensure uniform dispersion, stirred on a magnetic stirrer for more than 14 hours until a uniform solution was formed, and ultrasonicated again for 20 minutes before electrospinning. Piezoelectric nanofibers were then prepared based on the electrospinning method, with spinning parameters: voltage 9-10kV, injection rate 20μL / min, receiving distance 20cm, drum speed 200rpm, and environmental conditions maintained at 20-25°C and 25-30% humidity. To induce the formation of hydrogel nanofibers, the dried GelMA nanofibers with T-BTO added were soaked in a photocrosslinking solution (Irgacure 2959 dissolved in anhydrous ethanol, the solution concentration was 10% (w / v)) and irradiated with 365nm ultraviolet light for 100min to induce crosslinking. Subsequently, the fibers were washed with anhydrous ethanol to remove excess photoinitiator to obtain piezoelectric hydrogel nanofibers.

[0052] ②TA functional modified hydrogel nanofibers: dissolve tannic acid (TA, 15 mg / mL) in Tris-HCl (10 mM, pH 8.5) buffer to prepare a TA mixed solution; then immerse the piezoelectric hydrogel nanofibers in the solution and gently oscillate at room temperature for 15 hours with an oscillation frequency of 150 rpm; take out the hydrogel nanofibers and wash them with ultrapure water for several times to obtain a piezoelectric hydrogel fiber patch modified with TA function.

[0053] Example 3

[0054] ① GelMA nanofiber bundles were prepared by stable jet electrospinning technology: GelMA (substitution degree of 75%) was weighed and dissolved in HFIP solution to prepare a spinning solution with a concentration of 15% (w / v). In order to give GelMA hydrogel nanofibers piezoelectric properties, 20% (w / v) tetragonal barium titanate nanoparticles (T-BTO) were added to the spinning solution, and then ultrasonicated for 25 minutes to ensure uniform dispersion, stirred on a magnetic stirrer for more than 10 hours until a uniform solution was formed, and ultrasonicated again for 25 minutes before electrospinning. Piezoelectric nanofibers were then prepared based on the electrospinning method, with spinning parameters: voltage 9-10kV, injection rate 20μL / min, receiving distance 20cm, drum speed 200rpm, and environmental conditions maintained at 20-25°C and 25-30% humidity. To induce the formation of hydrogel nanofibers, the dried GelMA nanofibers with T-BTO added were soaked in a photocrosslinking solution (Irgacure 2959 dissolved in anhydrous ethanol, the solution concentration was 15% (w / v)) and irradiated with 365nm ultraviolet light for 200min to induce crosslinking. Subsequently, the fibers were washed with anhydrous ethanol to remove excess photoinitiator to obtain piezoelectric hydrogel nanofibers.

[0055] ②TA functional modified hydrogel nanofibers: dissolve tannic acid (TA, 20 mg / mL) in Tris-HCl (10 mM, pH 8.5) buffer to prepare a TA mixed solution; then immerse the piezoelectric hydrogel nanofibers in the solution and gently oscillate at room temperature for 15 h at an oscillation frequency of 200 rpm; take out the hydrogel nanofibers and wash them with ultrapure water for several times to obtain a piezoelectric hydrogel fiber patch modified with TA function.

[0056] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a motion-driven self-powered hydrogel nanofiber patch, characterized in that: The method comprises the following steps: (1) preparing a spinning solution, wherein the solute is GelMA and tetragonal barium titanate nanoparticles, and obtaining piezoelectric nanofibers after electrospinning; (2) drying the piezoelectric nanofibers in step (1), and then immersing the dried piezoelectric nanofibers in a photo-crosslinking solution to crosslink them under ultraviolet irradiation to obtain piezoelectric hydrogel nanofibers; (3) Immersing the piezoelectric hydrogel nanofibers in a TA mixed solution, and taking them out after immersion, to obtain a functionally modified piezoelectric hydrogel fiber patch, which is the motion-driven self-powered hydrogel nanofiber patch.

2. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (1), the degree of substitution of GelMA is 0-100%.

3. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (1), the added amount of tetragonal barium titanate nanoparticles is 0 to 50% (w / v).

4. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (1), the solvent of the spinning solution is HFIP, and the concentration of the spinning solution is 1 to 20% (w / v).

5. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (1), the electrospinning parameters are: voltage 9-10 kV, injection rate 20 μL / min, receiving distance 20 cm, drum speed 200 rpm, and environmental conditions maintained at 20-25° C. and 25-30% humidity.

6. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (2), the photocrosslinking solution is prepared by dissolving a photoinitiator in anhydrous ethanol, and the concentration of the photocrosslinking agent solution is 1-20% (w / v); preferably, the photoinitiator is Irgacure 2959.

7. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (2), during the cross-linking treatment, 365 nm ultraviolet irradiation is performed for 1 to 300 min.

8. The method for preparing the motion-driven self-powered hydrogel nanofiber patch according to claim 1, characterized in that: In step (3), the TA (tannic acid) mixed solution is prepared by dissolving tannic acid in Tris-HCl buffer, with a concentration of 1 to 20 mg / mL.

9. A motion-driven self-powered hydrogel nanofiber patch prepared by the method according to any one of claims 1 to 8.

10. Use of the motion-driven self-powered hydrogel nanofiber patch according to claim 9 in the preparation of medical supplies.

Citation Information

Patent Citations

  • Fiber membrane for transmitting sound and inducing tympanic membrane regeneration as well as preparation method and application of fiber membrane

    CN113209388A

  • Oriented hydrogel dressing with piezoelectric effect and preparation method and application thereof

    CN117100903A

  • Antibacterial dressing capable of autonomously generating power and preparation method thereof

    CN118767198A

  • Optical biomodule for detection of diseases at an early onset

    US12135286B1

  • Tissue scaffolds and constructs

    US20230390461A1